2004
DOI: 10.1246/cl.2004.176
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Micro and Nanoscale Patterns of Monolayer Templates for Position Selective Immobilization of Oligonucleotide Using Ultraviolet and Electron Beam Lithography

Abstract: Formation of organosilane monolayer templates using ultraviolet and electron-beam (EB) lithography was investigated. The oligonucleotides were covalently immobilized with high selectivity only to the amino-monolayer modified regions locally formed on the template surfaces at micro and nanometer scale. By using EB lithography, patterned immobilization in nanometer scale, as small as 20 nm, was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The water contact angle of the ODMS-modified surface was approximately 95º, indicating that the surface was successfully modified by hydrophobic ODMS. By using ellipsometry, we found that the thickness of the ODMS layer was approximately 20 Å, which corresponds to the thickness of the ODMS monolayer specified in a previous report 13 . The recombinant Mms6 and BSA were then attached to the substrate through the hydrophobic interactions between these proteins and the ODMS monolayer that have been reported previously 14 .…”
Section: Modification Of the Silicon Substrate With Mms6supporting
confidence: 79%
“…The water contact angle of the ODMS-modified surface was approximately 95º, indicating that the surface was successfully modified by hydrophobic ODMS. By using ellipsometry, we found that the thickness of the ODMS layer was approximately 20 Å, which corresponds to the thickness of the ODMS monolayer specified in a previous report 13 . The recombinant Mms6 and BSA were then attached to the substrate through the hydrophobic interactions between these proteins and the ODMS monolayer that have been reported previously 14 .…”
Section: Modification Of the Silicon Substrate With Mms6supporting
confidence: 79%
“…For patterning of the molecules, methods including microcontact printing, ink-jet delivery, dip-pen nanolithography, and nano-manipulation using scanning probe microscopy have been proposed. On the other hand, we investigated the process for fabricating molecular templates at micro and nano scales using UV and electron-beam lithography [5,38,39]. These processes aid the controlled formation of SAMs having various functional groups under self-assembling conditions, with a precise position selectivity to form active and passive sites for immobilization of biomolecules.…”
Section: Attachment Of Biomolecules Onto the Recognition Regionmentioning
confidence: 99%
“…Nanopatterning of SAM combined with the EBL produces an organic template for various nanofabrication of biosensors [83, 94]. Biomolecules such as DNAs and proteins are immobilized on nano-patterned organic templates provided by EBL [95, 96]. DNA could be immobilized via sequence-specific DNA hybridization on EBL-nanopatterned surfaces.…”
Section: Nanoscale Patterning Of Biomolecules Using Molecular Recognimentioning
confidence: 99%